2019
DOI: 10.1016/j.paid.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Personality profiles and persuasion: An exploratory study investigating the role of the Big-5, Type D personality and the Dark Triad on susceptibility to persuasion

Abstract: The present study investigated the relationship between personality profiles and susceptibility to persuasion. Participants (N = 316) were recruited for an online questionnaire and asked to complete self-reported measures of their personality-Big-5, Dark Triad and Type D. Individual differences in susceptibility to persuasion were also explored using Cialdini's model of persuasion. Latent profile analysis identified three distinct profiles which were labelled Socially Apt, Fearful and Malevolent. These profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 63 publications
(54 reference statements)
1
13
0
3
Order By: Relevance
“…Past studies have reported similar results (Alkiş and Taşkaya Temizel 2015;Wall et al 2019), but our sample did not find a correlation between reciprocation and authority, which was comparatively strong in both of the studies mentioned above. However, similar to our results, a strong positive correlation between consensus and liking has been previously reported (Wall et al 2019). Interestingly, statistically significant correlations were more often found among men.…”
Section: Susceptibility To Influence Strategies In the Finnish University Samplesupporting
confidence: 62%
See 3 more Smart Citations
“…Past studies have reported similar results (Alkiş and Taşkaya Temizel 2015;Wall et al 2019), but our sample did not find a correlation between reciprocation and authority, which was comparatively strong in both of the studies mentioned above. However, similar to our results, a strong positive correlation between consensus and liking has been previously reported (Wall et al 2019). Interestingly, statistically significant correlations were more often found among men.…”
Section: Susceptibility To Influence Strategies In the Finnish University Samplesupporting
confidence: 62%
“…A 'socially apt' profile high in extraversion, agreeableness and conscientiousness was highly susceptible to commitment, indicating preference for consistency with previous behaviors. 'Malevolent' profiles that scored high in extraversion and negative affectivity also manifested so-called dark triad traits and were susceptible to scarcity (Wall et al 2019). The importance of culture to the creation of susceptibility to scarcity is supported by a recent study that concluded that scarcity is unique to humans and is learned when children develop their cognitive skills in social interaction (John et al 2018).…”
Section: Persuasion and Personalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Os tipos de personalidades foram pioneiramente descritos por cardiologistas americanos na década de 50, como indicador para estimar o risco de doenças cardiovasculares. Deste modo, na personalidade tipo D, tem-se como características sobrepujantes, o temor da rejeição, a tendência ao desespero, o humor melancólico e a autopercepção negativizada (WALL, 2019). Outrossim, o psicólogo belga e criador de uma escala psicométrica de personalidade, Johan Denollet, também destaca a irritabilidade como um dos caracteres mais preponderantes desse perfil de personalidade, associando este indício à performance social dos indivíduos tipo D.…”
Section: Fundamentação Teóricaunclassified